2001
DOI: 10.1002/jcu.10022
|View full text |Cite
|
Sign up to set email alerts
|

Sonographic appearances of cervical lymph nodes: Variations by age and sex

Abstract: This study provides information about the sonographic appearances of and variations between normal cervical lymph nodes. The presence of an increased number of cervical lymph nodes and the absence of an echogenic hilum within the nodes may help to identify an abnormality more in older patients than in younger patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0
3

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(29 citation statements)
references
References 26 publications
0
26
0
3
Order By: Relevance
“…The specificity of the round shape is in fact linked to the long axis (6,8). Similarly, the absence of fatty hilum is often seen in normal individuals, especially in young subjects and LNs located in level V (19). Interestingly, we found a sensitivity of 100%, indicating that the persistence of a fatty hilum is a major criteria that excludes malignancy.…”
Section: Discussionmentioning
confidence: 53%
“…The specificity of the round shape is in fact linked to the long axis (6,8). Similarly, the absence of fatty hilum is often seen in normal individuals, especially in young subjects and LNs located in level V (19). Interestingly, we found a sensitivity of 100%, indicating that the persistence of a fatty hilum is a major criteria that excludes malignancy.…”
Section: Discussionmentioning
confidence: 53%
“…A criterion that is frequently utilized to define lymph node enlargement is the smallest diameter > 4 mm (measured by means of ultrasonography) or 5 mm (CT) (14)(15)(16)(17) . However, enlarged lymph nodes are found on imaging studies of asymptomatic patients, with these same values (14,(18)(19)(20) . Even so, the literature commonly reports that lymph nodes are rarely seen at CT of children in the usual age range for WT (21) .…”
Section: Discussionmentioning
confidence: 70%
“…Malignant lymph nodes usually do not show echogenic hilus. However, it has been reported that echogenic hilus may also be found in malignant lymph nodes and small normal nodes [6,8]. Therefore, the presence or absence of echogenic hilus should not be used as a sole criterion for evaluating cervicofacial lymphadenopathy.…”
Section: Resultsmentioning
confidence: 99%